Macbeth - Shakespeare, William (New York : Simon & Schuster Paperbacks, 2013)
In 1603, James VI of Scotland ascended the English throne, becoming James I of England. London was alive with an interest in all things Scottish, and Shakespeare turned to Scottish history for material. He found a spectacle of violence and stories of traitors advised by witches and wizards, echoing James$1 (Bs belief in a connection between treason and witchcraft.s
Editors' preface -- Shakespeare's Macbeth -- Reading Shakespeare's language: Macbeth -- Shakespeare's Life -- Shakespeare's theater -- The publication of Shakespeare's plays -- An introduction to this text -- The tragedy of Macbeth.
Keywords: SCOTLAND -- DRAMA